Globalization and the New Normal - Carare, Alina (IMF Working Papers; Working Paper ;, 2018)
This study expands the empirical specification of Cerra and Saxena (2008), and allows short-term output growth regimes to be determined by globalization. Relying on a non-linear dynamic panel representation, it reconciles the earlier results in the literature regarding the two opposite narratives of the effects of globalization on output growth. Countries experience higher growth, on average, the more open and integrated they are into the world. However, once they reach a certain globalization threshold (endogenously estimated), countries may also experience a new normal, persistently lower short-term output growth following a financial crisis. The benefits, as well as vulnerabilities, accrue earlier in the globalization process for low- and middle-income countries. To solely reap the globalization benefits on growth, sound policies should be in place to mitigate the negative effects stemming from increased vulnerabilities brought by globalization.